A 'whole of system' approach to compare options for CVD interventions in Counties Manukau - Timothy Kenealy; David Rees; Nicolette Sheridan; Allan Moffitt; Sarah Tibby; Jack Homer (Elsevier, 2012)
Abstract Objective: To assess the usefulness of a national and a local system dynamics model of cardiovascular disease to planning and funding decision makers. Methods: In an iterative process, an existing national model was populated with local data and presented to stakeholders in Counties Manukau, New Zealand. They explored the model's plausibility, usefulness and implications. Data were collected from 30 people using questionnaires, and from field notes and interviews; both were thematically analysed. Results: Potential users readily understood the model and actively engaged in discussing it. None disputed the overall model structure, but most wanted extensions to elaborate areas of specific interest to them. Local data made little qualitative difference to data interpretation but were nevertheless considered a necessary step to support confident local decisions. Conclusion: Some limitations to the model and its use were recognised, but users could allow for these and still derive use from the model to qualitatively compare decision options. Implications: The system dynamics modelling process is useful in complex systems and is likely to become established as part of the routinely used suite of tools used to support complex decisions in Counties Manukau District Health Board.